Monolayer whole adherent islets: A novel tool for studying drug-induced diabetic phenotypes in vitro - Makiko Kumagai-Braesch; Ming Yao; Nils Ågren; Ahmad Karadagi; Bo-Göran Ericzon; Anna Domogatskaya (PLoS ONE, 2025)
To understand the mechanisms of diabetes and develop novel drugs, various animal diabetes models as well as in vitro experimental systems have been established. Using isolated islets in vitro is associated with several problems: (1) discontinued blood microcirculation causes ischemia and central necrosis in isolated islets, (2) dissociation of islets into single cells reduces the total number of cells and impairs endocrine function. Here, we aim to establish a novel experimental method using isolated islets to characterize cell physiology and drug effects. We have developed a method to flatten islets into monolayers by culturing small, whole, non-disrupted mouse islets on laminin-521. In this culture, islet cells remain intact, and cell-cell junctions are not broken mechanically. Small mouse islets were cultured in a 96-well plate coated with laminin-521 for six days and then exposed to various concentrations of streptozotocin (STZ) for 24 hours. Monolayer islets exposed to 0.6 mM STZ-induced a metabolic diabetes-like phenotype, i.e., islet cell death, predominantly of beta cells, causing a shift in alpha-to-beta cell ratio. The stimulation index in a glucose-stimulated insulin secretion assay was reduced in STZ-treated islets. However, insulin production per beta cell did not change significantly. The monolayer whole islet assay format allows the extraction of quantitative data regarding endocrine cell populations, “endocrine sensitivity” (stimulation index), and “endocrine power” (amount of hormone secreted per cell). It is a novel, versatile, user-friendly, semi-automated, and financially attractive experimental platform.